Increasing Estrus Expression in Lactating Dairy Cows - J. A. Sauls; B. E. Voelz; J. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2016)
This report summarizes the use of various hormones in an attempt to induce greater estrus expression of lactating dairy cows. Average detection of estrus (<50%) in most U.S. dairy herds has been identified as a problem limiting reproductive efficiency. Detection of estrus plays an important role in reproductive management in U.S. dairy herds despite the adoption of fixed-time artificial insemination programs. When estrus was detected by an activity monitoring system or a rump-mounted device, supplementing cows with progesterone before induction of luteolysis resulted in greater intensity of estrus when compared with controls. In addition, administering estradiol cypionate at 24 h after induced luteolysis resulted in greater frequency of estrus expression compared with cows treated with testosterone propionate or controls when assessed by an activity monitor. Activity monitoring systems achieved heat-detection rates of approximately 70% (80% with estradiol) and are likely cost effective for herds achieving less than that level of heat detection.
Keywords: heat; estradiol; progesterone